2008
DOI: 10.1002/rsa.20234
|View full text |Cite
|
Sign up to set email alerts
|

Multiple choice tries and distributed hash tables

Abstract: Tries were introduced in 1960 by Fredkin as an efficient method for searching and sorting digital data. Recent years have seen a resurgence of interest in tries that find applications in dynamic hashing, conflict resolution algorithms, leader election algorithms, IP addresses lookup, Lempel-Ziv compression schemes, and distributed hash tables. In some of these applications, most notably in distributed hash tables one needs to design a well balanced trie, that is, a trie with the height as close as possible to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Please note that [2], [20], [21], [24], [25], and [27] were published shortly after the commencement of the project before its number was changed, therefore acknowledge the funding under the original grant number FA8655-07-1-3071. Finally, [19], [22], and [26] are recent enhanced versions of publications using some results and approaches developed within the former Grant FA8655-04-1-3074, and therefore acknowledge the funding under that grant number.…”
Section: Summary Of Technical Resultsmentioning
confidence: 99%
“…Please note that [2], [20], [21], [24], [25], and [27] were published shortly after the commencement of the project before its number was changed, therefore acknowledge the funding under the original grant number FA8655-07-1-3071. Finally, [19], [22], and [26] are recent enhanced versions of publications using some results and approaches developed within the former Grant FA8655-04-1-3074, and therefore acknowledge the funding under that grant number.…”
Section: Summary Of Technical Resultsmentioning
confidence: 99%
“…Azar et al [1] showed that the maximum load is reduced to ln ln n/ ln d + O(1) in the d-choice process where each ball is placed into the least loaded among d bins chosen i.u.r. Since the multiple choice paradigm was introduced in 1990's, a number of variants of the load balancing process have been studied [8,5,7,2,4].…”
Section: Introductionmentioning
confidence: 99%